HUBUNGAN BUDAYA ORGANISASI DAN MOTIVASI KERJA DENGAN KINERJA GURU SPK PAMULANG-TANGERANG SELATAN - Zuesty Haryana; Said Hutagaol; Hotmaulina Sihotang (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2019)
The formation of intelligence capabilities in education world besides the family as important role, it is school organisation. The school is an alternative educational service institution that has a vision, mission, goals and functions. To carry out its mission, realise its vision, achieve its goals, and carry out its functions, schools need professionals and resources that support both financially and non-financially to achieve common goals. Therefore this study seeks to uncover the relationship between organizational culture and work motivation with teacher performance measured individually or collectively in a school. This study was conducted on 47 teachers of SPK Pamulang-Tangerang Selatan with random sampling techniques. From the results of the comparison, Ho's decision was rejected, they are the relationship between organisational culture and teacher performance, and the relationship between work motivation with teacher performance. This is evidenced from the significant level value of 0.001 <α (0.05) = 0.05. Based on the result, it can be concluded that the null hypothesis was rejected, because the results of the hypothesis testing indicate that there is a positive and significant relationship between Organisational Culture, Work Motivation along with the Teacher’s Performance in SPK Pamulang-Tangerang Selatan.